Coal Industry Development Model - Bodnja A.L. (General Energy Institute of the National Academy of Sciences of Ukraine, 2000)
The model of optimal operating and development of the coal industry as the basic branch of Ukraine's energy sector has been proposed in the article. The set of methods for model calculations has been developed.